Homemaking for the Apocalypse - Anderson, Jill E. (Taylor & Francis Group, 2021)
Cover – Endorsement – Half Title – Series Page – Title Page – Copyright Page – Dedication – Table of Contents – Acknowledgements – Introduction: Homemaking for the Apocalypse: Compulsory Normativity, Banality, and Horror – 1. Die, Dig, or Get Out: Or, Stop Worrying and Love the Bomb – 2.
Description based on publisher supplied metadata and other sources
Keywords: American literature-20th century-History and criticism; Nuclear warfare-Psychological aspects; Horror tales; American-History and criticism; Cold War-Psychological aspects; Families in literature; Domestic relations in literature; Cold War in mass media; Apocalypse and popular culture; United States-Civilization-1945-; Electronic books